Advances in neural computation, machine learning, and cognitive research : selected papers from the XIX International Conference on Neuroinformatics, October 2-6, 2017, Moscow, Russia /: selected papers from the XIX International Conference on Neuroinformatics, October 2-6, 2017, Moscow, Russia. (2018) - Unknown
No abstract available